Traintown 3-D ultra (Bellevue, WA : Sierra Attractions, 1999)
Features more than thirty different Lionel model trains with animations, and more than seventy assignments.
Title from disc label.
"The virtual Lionel train game"--Container.
Production level cataloging.
Keywords: Railroads -- Models